2017
DOI: 10.1080/14740338.2017.1344639
|View full text |Cite
|
Sign up to set email alerts
|

Off-label prescribing for children with chronic diseases in Nigeria; findings and implications

Abstract: Off-label prescribing for children with epilepsy, asthma and sickle cell anaemia occurs. Encouragingly, the overall rate appears low in Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…In a hospital setting, the disease and patient’s condition are of primary importance. Oshikoya et al [ 99 ] reported a low rate of off-label prescriptions in the chronic treatment of epilepsy, asthma, and sickle cell anemia, while in the most vulnerable group of NICU patients, the percentage skyrocketed to 94% [ 90 ]. Comparative data on the extent of off-label prescribing in children 0 to 18 years in different countries and regions, published in medical literature from 2012 to 2022, are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In a hospital setting, the disease and patient’s condition are of primary importance. Oshikoya et al [ 99 ] reported a low rate of off-label prescriptions in the chronic treatment of epilepsy, asthma, and sickle cell anemia, while in the most vulnerable group of NICU patients, the percentage skyrocketed to 94% [ 90 ]. Comparative data on the extent of off-label prescribing in children 0 to 18 years in different countries and regions, published in medical literature from 2012 to 2022, are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This includes key areas such as the integration of biomedical information enhancing for instance the rational use of medicines which will benefit all SSA communities [60]. Key areas will also include assessing prescribing against agreed national guidelines including using tools such as DU90% as well as assessing the extent of off label prescribing and potential drug-drug interactions as a prelude to developing future activities based on on-line support [61][62][63][64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo espanhol realizado em uma unidade de cuidados intensivos demonstrou que, do total de prescrições avaliadas, 8,6% estavam sendo prescritas em condições não licenciadas, e aproximadamente 54% estavam sendo utilizadas de forma off-label 9 . Na África do Sul, identificou-se que 7% dos receituários médicos ocorrem de maneira off-label nos ambientes ambulatoriais geral e altamente especializados, semelhante à porcentagem encontrada em pesquisa realizada na Nigéria, em que situações como essas acontecem em 7,7% dos casos 18,34 . Em pesquisa realizada em hospitais terciários da Coreia do Sul, foi apontado um percentual bastante elevado dessas prescrições, em que mais de 80% dos pacientes receberam um ou mais medicamentos off-label 24 .…”
Section: Prevalência Do Uso De Medicamentos Off-label E Não Licenciadosunclassified
“…Um medicamento classifica-se como off-label pela frequência ou dosagem quando esses parâmetros estão em discordância com o que está especificado na bula, sendo utilizados em dose e/ou frequência maiores ou menores do que o aprovado. Dentre os estudos que relatam os produtos utilizados dessa forma (Quadro 4), destacam-se a cefotaxima e a gentamicina, pertencentes à classe terapêutica dos anti-infecciosos de uso sistêmico 6,9,15,16,18,20,22…”
Section: Frequência E Dosagemunclassified